Characterization of Partial Coding Region Fibroin Gene on Wild Silkmoth Cricula trifenestrata Helfer (Lepidoptera: Saturniidae) - Suriana Suriana; D D Solihin; R R Noor; A M Thohari (Media Peternakan, 2011)
The study was conducted to characterize coding region of wild silkmoth C. trifenestrata partial fibroin gene, and detect these gene potential as molecular marker. A total of six larvae C. trifenestrata were collected from Bogor, Purwakarta and Bantul Regency. Genomic DNA was extracted from silk gland individual larvae, then amplified by PCR method and sequenced. DNA sequenced result was 986 nucleotide partial fibroin gene of C. trifenestrata, which are comprising complete coding region of first exon (42 nucleotide), an intron (113 nucleotide), and partial of second was exon (831 nucleotide). Only coding region was characterized. Results showed that first exon very conserved in C. trifenestrata. These gene consisted of 31%, thymine, 28% guanine, 21% cytosine, and 19% adenine. Cytosine and thymine (sites of 25th and 35th respectively) were marker for C. trifenestrata species. The first exon encoding 14 amino acids. Valine amino acid (12th site) was marker to the species C. trifenestrata. The partial second exon consisted of guanine (32.7%), alanine (26.5%), thymine (21%) and cytosine (19.7%). These region encoded 277 amino acids, which were dominated by the alanine (27.8%) and glycine (21.66%). Alanine formed polyalanine sequence with different motifs namely: AAAAAAASS, AAAAAAAAAAAGSSG, AAAAAAAAAAAAGSGTGFGGYDS, AAAAAAAAAAGSSGRGGYDGVDGGYGSGSS, and AAAAAAAAAAAAGSSGRGLGGYDGWVDDGYGSGSGS.